Validation of EUREKA-2/RR Code for Analysis of Pulsing Parameters of TRIGA Mark II Research Reactor in Bangladesh - Altaf, M. H.; Badrun, N. H.; H. Khan, M. J. (The Nucleus, 2014)
Some parametric studies on pulsing mode for fresh core of TRIGA Mark II research reactor in AERE, Savar, have been carried out with coupled thermal-hydraulics code EUREKA-2/RR in association with neutronics code SRAC. At the beginning, role of some important parameters in pulsing like delayed neutron fraction (Î²eff) and reactivity insertion have been studied keeping prompt neutron life time (lp) fixed at 33.4 Âµ-sec. After a series of experiments, we found that the pulsing peak that is consistent with the Safety Analysis Report (SAR) is for the delayed neutron fraction (Î²eff) of 0.007 and reactivity insertion of 2. Study has determined the pulsing peak of the fresh core for this particular condition to be 857.86 MW which is 852 MW according to SAR. Experiment also shows the pulsing peak increases with the increase of reactivity insertion whereas decreases with increase of delayed neutron fraction. With the utilization of the particular values of these parameters, pulsing parameters like prompt energy released, reactor period, pulse width at half maxima, alongwith safety parameters including peak power and clad maximum temperature, have been analyzed. The clad maximum temperature for fresh core is simulated to be 144.54 MW, which is much less than the SAR Value, ensuring the validity of codes and the safety of pulsing in that particular condition.